Resistance Switching Characteristics in ZnO-Based Nonvolatile Memory Devices - Fu-Chien Chiu (Advances in Materials Science and Engineering)
Bipolar resistance switching characteristics are demonstrated in Pt/ZnO/Pt nonvolatile memory devices. A negative differential resistance or snapback characteristic can be observed when the memory device switches from a high resistance state to a low resistance state due to the formation of filamentary conducting path. The dependence of pulse width and temperature on set/reset voltages was examined in this work. The exponentially decreasing trend of set/reset voltage with increasing pulse width is observed except when pulse width is larger than 1 s. Hence, to switch the ZnO memory devices, a minimum set/reset voltage is required. The set voltage decreases linearly with the temperature whereas the reset voltage is nearly temperature-independent. In addition, the ac cycling endurance can be over 106 switching cycles, whereas, the dependence of HRS/LRS resistance distribution indicates that a significant memory window closure may take place after about 102  dc switching cycles.